Mixed Ligand Complexes of Alkali Metal Salts of Organic Acids with o-Amino Thiophenol - Prakash, D.; Anwar Hussain, Syed; PD. Yadav, Siteshwar; Ku. Gupta, Anju (Asian Journal of Chemistry, 2010)
Complexes of the type ML·HL' have been synthesised and characterised, where M = Li, Na or K, HL' = o-amino thiophenol, L = deprotonated o-nitro phenol, 2,4-dinitrophenol, 1-nitroso-2- naphthol and 8-hydroxy quinoline. All the complexes have been found to be four-coordinated in which ligand o-amino thiophenol is coordinated through N-atom of amino group and S-atom of the thiol group forming five-membered stable chelation.